The Implication of Flipped Learning Model in Tertiary Critical Reading Class - Atmanegara, Yunani; Dianti, Rahma (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study investigated the implication of Flipped Learning Model toward tertiary students’ critical reading skill. Classroom action research was carried out to conduct the study. Critical reading test, observation of students’ learning participation outside and inside class, and interview were administered to gather the data. This study used descriptive analysis. Students’ prior critical reading skill was considerably low. They did not have self-initiative to practice their reading skill. After implementing this model for three cycles, progress on their critical reading could be noticed. Flipped Learning Model could trigger students’ learning participation both outside and inside classrooms. Yet, students still needed teacher’s assistance to direct their learning process. Flipped model of instruction encouraged students to be able to analyze and evaluate the texts. However, students still had difficulty in internalizing the information to formulate ideas as creating skill needs more practice to achieve. Appropriate learning materials, students’ awareness, and environmental supports influenced the implication of Flipped Learning Model implementation.